DAMPAK PILPRES TERHADAP GEJOLAK EKONOMI: EFEK PERBEDAAN 3 PEMILU MASA CAPRES TERHADAP VOLATILITAS IHSG - Desi Wahyuni (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2019)
Political events can generate positive or negative sentiments towards investors that will affect the investment climate in Indonesia. This study aims to examine the difference in the composite stock price index (IHSG) between before and after domestic political events, namely the general election of president and vice president in 2009, 2014, 2019. This study uses composite share price index data at the time daily closure with a window period of twenty-six before and after general elections in 2009, twenty-five before and after general elections in 2014, and twenty-three before and after general elections in 2019. Data analysis techniques use paired sample t- test. The results did not differ the impact of the presidential election on economic turmoil in the 3 presidential elections against the JCI volatility. This is because the market reaction will tend to wait and see certainty from selected leaders later with policies that are able to influence the economy towards a better direction.